An Analysis of Color Psychology and the Correlation with Buyer Behavior - Loviena Dasture (International Journal of Advanced Science and Technology, 2020)
Color Psychology is a field of study that seeks to understand the effects color has on a consumer’s actions and decisions. In marketing, different colors may have an influence on how consumers view brands, which may not be obvious. It is an essential area to study when developing marketing strategies, developing a new company, or simply rebranding an existing venture. It is known that while certain colors can ignite a sense of excitement in our minds, there are certain hues that can conversely be ultimately soothing in nature. Say you're a fashion house trying to connect with a young audience or a medical store trying to build trust amongst its patrons, you can research color definitions to help you attract and relate to your ideal customer in a better way. Color psychology can be used to help build a powerful, relatable brand. I aim to explore the effects of color psychology on the minds of consumers globally and understand the process of how successful marketers leverage this to their advantage.  Furthermore, I wish to highlight the rationale behind the judgements made by consumers while purchasing a product, based on the color scheme of the same; and the emotions they undergo as they make such decisions on a daily basis. The association between color psychology and customer behavior is at the core of most commercial practices in the business world. Empirical and theoretical literature suggests that color psychology is influential in evaluating the efficacy of marketing practices, especially when properly incorporated into the development and delivery strategies of the enterprise. There are different interpretations of color as determined by consumer beliefs, culture and attitudes. The aim of the paper is to analyze the correlation linking color psychology and consumer behavior patterns. Variations in customer purchasing habits across the globe have intensified as a result of diverse perceptions of marketing mix features.